TECHNOLOGY’S ROLE IN LESSON PLAN DESIGN FOR ENGLISH AS A FOREIGN LANGUAGE (EFL) IN BLENDED LEARNING - Windi Azahra; Maurizka Putri Muliana (Universitas Wiralodra, 2025)
This study investigates the role of technology in lesson plan design for English as a Foreign Language (EFL) instruction within blended learning environments. Using a qualitative literature review approach, data were gathered from peer-reviewed journal articles indexed in Scopus and ERIC from 2021 to 2025. The objective was to identify the impact of digital tools on the lesson planning process and EFL learning outcomes. The findings show that platforms such as Google Classroom, Moodle, Zoom, Canva, and Web 2.0 tools are frequently utilized due to their capacity to support collaboration, personalized learning, and the impact of content delivery. The integration of technology allows teachers to design more interactive, flexible, and student-centered lesson plans that align with 21st-century educational demands. However, the study also highlights challenges such as digital literacy gaps and unequal access to technology. The results underscore the necessity for ongoing teacher training and institutional support to ensure the impact of technology integration. In conclusion, while digital tools significantly enhance EFL instruction in blended settings, their success depends on thoughtful pedagogical implementation. Future research should explore emerging technologies and address implementation barriers in diverse educational contexts.